THE ETHICS OF DAKWAH ON SOCIAL MEDIA AS SEEN IN BUYA HAMKA'S TAFSIR AL-AZHAR THROUGH THE STUDY OF THE QUR'AN SURAT AN-NISA' VERSES 148-149 - Abdullah, Subhan; Sugiarto, Fitrah; Ilham Wahyudi, Ahmad; Nurfanita, Sania (Universitas Islam Negeri (UIN) Mataram, 2022)
This study aims to explore various values of Islamic teachings that can be used as a code of ethics for dakwah on social media through the study of the Qur'an, Surat an-Nisa, verses 148–149 in Tafsir al-Azhar by Buya Hamka. This is a qualitative study conducted in the form of library research. The primary data sources used are the Qur'an and Buya Hamka's Tafsir al-Azhar. While the secondary data sources used are various scientific journals relevant to the study's main topic, This research includes conceptual research with a philosophical-normative approach. While the nature of this research approach is descriptive-analytical and prescriptive, The results of this study show that there are various values in Islamic teachings that can be used as ethical values for dakwah on social media. These ethical values prioritize language politeness in dakwah by implementing the Qawlan Layyinan concept with courtesy and courtesy without displaying violence and hatred to the community, having a good and beautiful temperament in both speech and deeds